A historical theology of the Hebrew Bible - Schmid, Konrad 1965- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2019)
A. Introduction. Is there a theology of the Hebrew Bible? -- B. The use of the concept of theology in relation to the Bible. The premodern conception of theology: from mythology to systematic doctrine -- The Reformation's reconstrual of the concept of theology -- From biblical theology to the theology of the Old Testament -- The romantic devaluation of the concept of theology -- The reception of the concept of theology in Judaism -- The devaluation of the concept of religion in neo-orthodox theology -- Developments since the mid-twentieth century -- Implicit theologies in the Hebrew Bible and the search for a theology of the Hebrew Bible -- C. Hebrew Bible and Old Testament. The pluriformity of the tradition -- The Tanakh as the Hebrew Bible -- Reception and transformation into the Old Testament -- The meaning and relativity of the canon for a theology of the Hebrew Bible -- D. Methodological reflections. Comparative definitions -- Fundamental methodological choices -- E. Theologies of extant Hebrew Bibles and Old Testaments. Hebrew Bibles in Judaism and their theologies -- Old Testaments and their theologies -- F. Theologies of the three parts of the canon and their collections. Torah -- Nevi'im -- Ketuvim -- G. The principal theological guidelines in the literary history of the Hebrew Bible. The Hebrew Bible on the way to its theology -- The destruction of the Northern Kingdom in 722 BCE -- The preservation of Jerusalem in 701 BCE -- The reinterpretation of Assyrian imperial ideology -- The destruction of Judah in 587 BCE -- The theological reception of Persian imperial ideology -- The destruction of the Persian Empire in 333-331 BCE -- Confrontations with the Maccabean crisis (167-164 BCE) and the question of the end of the theological history of the Hebrew Bible -- H. Themes in the theology of the Hebrew Bible. Literary genres and forms of theological statements in the Hebrew Bible -- Perceptions and impressions of God -- From counterworld to everyday world: the basic precepts of life -- Divine intervention in history -- Political theology -- Law and righteousness -- Temple worship and sacrifice -- People of a nation, people of God, and the individual -- Monarchy, theocracy, and anticipation of a ruler -- Zion and Sinai -- Interpretations of humanity -- Diversity and unity in the theology of the Hebrew Bible -- I. The question of a Jewish theology of the Hebrew Bible or a Christian theology of the Old Testament. The Hebrew Bible and Judaism -- The Old Testament and Christianity.
Includes bibliographical references and indexes
Keywords: Bible -- Theology -- History; Bible; Bible ; Old Testament ; fast ; (OCoLC)fst01808092; RELIGION / Christian Theology / Systematic ; bisacsh; RELIGION / Christianity / General ; bisacsh; Theology ; fast ; (OCoLC)fst01149559; History ; fast ; (OCoLC)fst01411628; RELIGION ; Christian Theology ; Systematic; RELIGION ; Christianity ; General; Theology; History; Electronic books